Penerapan Model Pembelajaran Talking Stick Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPAS Kelas 3 SD Negeri Cimahi 02 - Yesi indriani; Sally Pratiwi; Rinaldi Yusup (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was prompted by the low learning outcomes in Natural and Social Sciences (IPAS) among third-grade students at SD Negeri Cimahi 02. The core problem was a conventional, teacher-centered learning process that resulted in student passivity and low concept comprehension, with only 40% of students achieving learning completeness. This study aimed to improve these IPAS learning outcomes by implementing the Talking Stick cooperative learning model to create a more active and student-centered environment. The research method employed was Classroom Action Research (CAR), conducted over two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects were the third-grade students of the aforementioned school. Data were collected through learning outcome tests, classroom observation sheets, and documentation. The results showed a significant improvement. The students' average score increased from an initial 53.7 to 75.2 in the first cycle and further to 85.7 in the second cycle. Consequently, student learning completeness rose from 25% in the pre-test to 77% after Cycle I, ultimately reaching 100% at the end of Cycle II. This demonstrates that the Talking Stick model effectively enhances student learning outcomes in IPAS.